The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1755-5949.2011.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

From Hypertension to Stroke: Mechanisms and Potential Prevention Strategies

Abstract: SUMMARYStroke is a major cause of disability and death worldwide. Prevention aimed at risk factors of stroke is the most effective strategy to curb the stroke pandemic. Hypertension is one of the most important risk factors for stroke. Despite the substantial evidence of the benefits of lowering blood pressure, conventional treatment does not normalize the burden of major cardiovascular events in patients with hypertension. Fully understanding the factors involved in the hypertension-induced stroke helps to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 157 publications
(149 reference statements)
2
65
0
3
Order By: Relevance
“…Stroke is a major cause of disability and death worldwide. Prevention aimed at risk factors of stroke is the most effective strategy to curb the stroke pandemic [35]. Genetic research represents a promising tool for stroke, especially CSVD patients, in both pathway of pathogenesis and the search for new molecular preventive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a major cause of disability and death worldwide. Prevention aimed at risk factors of stroke is the most effective strategy to curb the stroke pandemic [35]. Genetic research represents a promising tool for stroke, especially CSVD patients, in both pathway of pathogenesis and the search for new molecular preventive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our data showed that DR can promote protection against ischemic cerebral injury [4]. We further concluded that the restoration of arterial baroreflex, one of the most important regulators of cardiovascular functions [5,6], involved in the protective effect of DR against stroke [4]. However, the mechanism of DR on the restoration of arterial baroreflex is unclear.…”
mentioning
confidence: 82%
“…Hypertension is an important risk factor of atherosclerosis [1-3] and stroke [4,5]. There are more evidences showing that carotid atherosclerosis increases risk of ischemic stroke [6,7].…”
Section: Backgroundsmentioning
confidence: 99%